A Traffic Monitoring Based on Vehicle Density Estimation and Analysis for a Mixed Traffic Flow in a Transport Cross-road - Nguyen, Viet Hung; Nguyen, Tien Dzung (Old Journal, 2017)
The Traffic Monitoring System (TMS) is an important element in an Intelligent Transportation Sysstem (ITS) for a real-time traffict flow control, especially in a developing country like Vietnam with a mixed traffic flow of vehicles including motorcycles and cars. In our previous research work, the density and length of the vehicles occupied on the road have been determined in the area viewed by a mounted camera on the road. However in this paper, a proper method for traffict flow control in the actual transport scenario in Vietnam is proposed, which monitors vehicle density in the area beyond and in front of traffict lights, as well as in the cross-road area from the mounted camera to estimate the traffic density. The system implementation and experimental results showed the efficiency of the proposed method compared to other convenient ones, where the traffic light signals are fully controlled by the estimated vehicle density captured by the system camera.